Noninvasive Immuno-PET Imaging of CD8+ T Cell Behavior in Influenza A Virus-Infected Mice - Rothlauf, Paul W.; Li, Zeyang; Pishesha, Novalia; Xie, Yushu Joy; Woodham, Andrew W.; Bousbaine, Djenet; Kolifrath, Stephen C.; Verschoor, Vincent L.; Ploegh, Hidde L. (Frontiers in Immunology, 2021)
Immuno-positron emission tomography (immuno-PET) is a noninvasive imaging method that enables tracking of immune cells in living animals. We used a nanobody that recognizes mouse CD8α and labeled it with 89Zr to image mouse CD8+ T cells in the course of an infection with influenza A virus (IAV). The CD8+ signal showed a strong increase in the mediastinal lymph node (MLN) and thymus as early as 4 days post-infection (dpi), and as early as 6 dpi in the lungs. Over the course of the infection, CD8+ T cells were at first distributed diffusely throughout the lungs and then accumulated more selectively in specific regions of the lungs. These distributions correlated with morbidity as mice reached the peak of weight loss over this interval. CD8+ T cells obtained from control or IAV-infected mice showed a difference in their distribution and migration when comparing their fate upon labeling ex vivo with 89Zr-labeled anti CD8α nanobody and transfer into infected versus control animals. CD8+ T cells from infected mice, upon transfer, appear to be trained to persist in the lungs, even of uninfected mice. Immuno-PET imaging thus allows noninvasive, dynamic monitoring of the immune response to infectious agents in living animals.